A Case Analysis On Digi Com Bhd - Muchelule, Linda Omutiti (2004)
This project paper is a case study which will provide an in-depth analysis into DIGI's business level strategies and how they can be formulated in order to maintain a competitive level strategies and how they can be formulated in order to maintain a competitive edge against its adversaries in the same business environment.